Efektivitas Neurofeedback Training Terhadap Komunikasi dan Stress Pada Anak Autis Di Pusat Kajian Psikologi Magister Psikologi Pascasarjana Universitas Medan Area - Nawal El Mutawakkil; Sri Milfyetty; Risydah Fadilah (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
This study aims to test the effectiveness of Neurofeedback Training in overcoming communication problems and stress in children with autism. This study used a Quasi Experiment One Group Pretest-Posttesta Design method. The sampling technique was using purposive sampling and the research sample was 1 person. Methods of data collection in this study using a brain wave effectiveness measurement instrument called Electroencephalography. The data analysis in this research resulted in two types of data, namely qualitative data and quantitative data. Quantitative data is the result of scores and graphs of measuring brain waves of autistic children through Neurofeedback, while qualitative data is the result of assessment using DSM V, observation results, reports and interviews. The hypothesis proposed is that Neurofeedback Training is effective in overcoming communication problems and stress in children with autism. and the conclusions in this study are: 1. Neurofeedback training effectively improves communication in children with autism, this is shown by increasing the SMR value from 3Hz to 5Hz. 2. Neurofeedback training is effective in reducing stress in children with autism, this is addressed through the Deff ratio of the balance between the left brain and the right brain which was initially 15% to 3.5%. 3. Neurofeedback training effectively improves communication and reduces stress in children with autism, this is addressed through the Alfha results of 18Hz, 5Hz Sensorymotor Rhytim value and 13Hz Beta value,  Deff The balance ratio of the left brain and right brain which was initially 15% to 3.5%. Based on this conclusion, the proposed hypothesis is accepted. And for future researchers who want to research Neurofeedback can use more subjects and on different disorders not only in children with autism.